High-throughput multi-antigen microfluidic fluorescence immunoassays. (January 2006) - Kartalov, Emil P.; Zhong, Jiang F.; Scherer, Axel; Quake, Stephen R.; Taylor, Clive R.; French Anderson, W.
Here we describe the development of a high-throughput multi-antigen microfluidic fluorescence immunoassay system. A 100-chamberpolydimethylsiloxane (PDMS) chip performs up to 5 tests for each of 10 samples. In this particular study system, the specificity of detection was demonstrated, and calibration curves were produced for C-reactive protein (CRP), prostate-specific antigen (PSA), ferritin, and vascular endothelial growth factor (VEGF). The measurements show sensitivity at and below clinically normal levels (with a signal-to-noise ratio >8 at as low as 10 pM antigen concentration). The chip uses 100 nLper sample for all tests. The developed system is an important step toward derivative immunoassay applications in scientific research and "point-of-care" testing in medicine.